Aquarelas: pinceladas de ironia nas crônicas do jovem Machado - Ramalho, Marcelo Pinto (2023)
This study aims to contribute to the composition of Machado de Assis’s literacy critical fortune by indicating that, although the chronicle is considered by some researchers as a minor genre, it offers a fertile field of studies, full of linguistic and literary aspects that deserve to be investigated. The dialogue in the chronicles written by Machado, especially in those from Aquarelas, the writer's first productions, is fed by markedly ironic elements, irony being an essential ally of Machado's chronicle, as it allows the observation of the singular forms that the author summons to explore the relationships between reality and criticism, which bring the reader closer to what is reported and operate inversion and displacement in relation to the usual understanding of events. The study of the peculiarly ironic metalanguage in a narrative key is also part of the investigations developed in this research, as well as the suggestion of some alternatives for the use of these linguistic resources as possible tools to bring young readers closer to the Machadian universe, thus arousing in these young and new readers the interest in the works of Machado de Assis